PEMBERDAYAAN EKONOMI SYARIAH BERBASIS SANTRIPRENEUR (Kasus: Di Pondok Pesantren Darul Hikmah Desa Gumantuk Maduran Lamongan) - ahmad munir hamid (LPPM UNISDA, 2023)
The santripreneur-based Sharia economic empowerment program is carried out at the Darul Hikmah Islamic Boarding School, Gumantuk Village, Maduran District, Lamongan Regency, a pesantren where to gain religious knowledge must be able to develop and adjust to the circumstances and needs of the community, especially in the field of economic and business development. Pokemon if run by the islamic boarding school was originally carried out in a mode to reduce the cost of food and education needs of the students because many costs were free (not paying anything). And after the activity lasted how many years it finally became a portrait and also a model applied in this islamic boarding school to increase the skills and also the ability of the students to not only master religious knowledge, but be independent in meeting economic needs that would later support in their households, in shia and proselytizing.This research uses a qualitative approach by being the object of the study are hotels in the islamic boarding school environment, such as caregivers and boards of trustees as well as teacher councils, through interviews and studies involving related parties and competent people in the field of islamic economic empowerment programs based on santripreneurs.From the results of the study, it was found that the preparation and strong mentality possessed by the personal students of Ponpes Darul Hikmah alumni after graduating from the pesantren, they tend to be more independent, have a strong mentality and like to work hard in carrying out economic activities in the community, and of course for islamic boarding schools this empowerment activity is quite helpful in an effort to ease the financial burden of the cottage to maintain some of the needs and needs of the students such as eating the needs of room cabinet equipment and also education costs, most of which are spent free of charge by the policy makers of the Darul Hikmah Islamic boarding school.Keywords: islamic economic empowerment, santripreneur.